THU0217 Safety of Infliximab Therapy in HbsAg Carriers with Rheumatoid Arthritis: A Prospective Study. (23rd January 2014) - Fang, L.; Pan, Y.; Guo, X.; Guo, X.; Liao, Z.; Lin, Z.; Gu, J.
Abstract : Background: Prevalence rate of hepatitis B virus (HBV) infection in China (13%) and many other developing countries are much higher than that in developed countries. When anti-TNF agents are more available and affordable in developing countries, the safety of anti-TNF therapy in terms of reactivation of hepatitis B infection needs more concern. No data from a prospective study focus on the use of TNF antagonists in patients with concurrent rheumatoid arthritis (RA) and HBV infection is available by now. Objectives: To evaluate the influence of infliximab on reactivation of HBV infection in HBsAg carriers with RA. Methods: In this 52 weeks observation, HBsAg carriers with active RA (DAS28>5.1) despite failed combined treatment with MTX and other non-biological DMARD were enrolled. Patients must have normal liver function prior to the study. All patients received therapy with infliximab (5mg/kg) and a low dose concomitant MTX (10-12.5mg). Lamivudin were prescribed preventively regardless of individual viral load. Pre-existing NSAIDs and corticosteroids (a maximum prednisone-dose equivalent of 10 mg/day) were allowed. During the study, serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) and HBV viral load (polymerase chain reaction) were monitored every 4 weeks. Increased viral load and abnormal liver function were managed and monitored according to expert opinion. Results: Nine female patients were recruited. At baseline, three patients (group 1) had increased viral load (4.3e4, 3.6e8, 5.6e5 copy/ml, respectively), and the other six patients (group 2) had normal viral load (<100 copy/ml). Only one patient from group 2 discontinued infliximab at week 6 due to ineffectiveness. Reactivation of hepatitis B occurred in one patient from group 1. At week 28, the patient (baseline viral load 5.6e5) underwent a mild increase of both ALT and AST (69 and 58 IU/L, respectively). A elevated viral load (8.9e8) and a HBV YMDD mutant were also found. The infliximab treatment continued. After prescription of Adefovir (combined with the pre-existing Lamivudin), both liver enzyme and viral load decreased to normal range in 12 weeks and remained normal. In the other two patients from group 1 and all patients from group 2, no significant increase of AST/ALT or viral load was seen during the 52 weeks follow-up. Conclusions: A aggressive Infliximab + MTX therapy may be a safe option for HBsAg carriers with DMARDs refractory RA. In order to reduce the risk of reactivation of hepatitis B infection, prophylaxis strategy with more effective anti-viral drugs is recommended. Large cohorts are highly needed to further evaluate the use of anti-TNF agents in patients with concurrent rheumatic diseases and different HBV infection status, including inactive and active infection. Disclosure of Interest: None Declared